Baitul Mal's social assistance effectiveness on community welfare in Aceh Tamiang - sari, juli dwina; Rahayu, Sri (ASNAF : Journal of Economic Welfare, Philantrophy, Zakat and Waqf, 2022)
Objectives – This study aims to see the effectiveness of Baitul Mal social assistance in improving the welfare of muzakki in Aceh Tamiang as well as the criteria needed to be considered in determining which community fit to receive Baitul Mal social assistance in Aceh Tamiang. Methods – The research method used is descriptive qualitative. Findings – a) The criteria for the Baitul Mal's social assistance recipients focus on only on three aspects, namely 1) compensation for fakir with severe disabilities (handicaps), compensation for the poor elderly, assistance for supporting the aqidah (cost of living) called Sehati Seaqidah Senif Muallaf program, and assistance for the poor with severe disabilities. 2) The effectiveness of social assistance program provided by Baitul Mal on the community welfare in Aceh Tamiang is complied to the Standard Operating Procedure (SOP) which addresses the social assistance distribution to the community. 3) in terms of determining the muzakki who are entitled to receive social assistance, Baitul Mal seek for an assistance from the village in regards to the data collection of muzzaki which meets to the criteria determined beforehand. Limitation – the minimum data available related to the utilization of social assistance that have been distributed to the muzzaki Practical Implication – The results of this study can be used as a reference for the government, especially zakat institutions in comprehending the level of effectiveness of Baitul Mal's social assistance on the welfare of the community.